Post-synthetic modification of divalent nickel acetate cubanes with carboxylates - Korzekwa, Jana; Scheurer, Andreas; Heinemann, Frank Wilhelm; Kroener, Wolfgang; Gieb, Klaus; Müller, Paul; Meyer, Karsten (Journal of Coordination Chemistry, 2017)
.
Keywords: N; O ligands; carboxylate ligands; cubanes; nickel; post-synthetic modification

Square-Planar Ruthenium(II) Complexes: Control of Spin State by Pincer Ligand Functionalization - Askevold, Bjorn; Khusniyarov, Marat; Kroener, Wolfgang; Gieb, Klaus; Müller, Paul; Herdtweck, Eberhardt; Heinemann, Frank Wilhelm; Diefenbach, Martin; Holthausen, Max C.; Vieru, Veacheslav; Chibotaru, Liviu F.; Schneider, Sven (Chemistry - A European Journal, 2015)
Functionalization of the PNP pincer ligand backbone allows for a comparison of the dialkyl amido, vinyl alkyl amido, and divinyl amido ruthenium(II) pincer complex series [RuClN(CH2CH2PtBu2)(2)], [RuClN(CHCHPtBu2)(CH2CH2PtBu2)], and [RuClN(CHCHPtBu2)(2)], in which the ruthenium( II) ions are in the extremely rare square-planar coordination geometry. Whereas the dialkylamido complex adopts an electronic singlet (S=0) ground state and energetically low-lying triplet (S=1) state, the vinyl alkyl amido and the divinyl amido complexes exhibit unusual triplet (S=1) ground states as confirmed by experimental and computational examination. However, essentially non-magnetic ground states arise for the two intermediate-spin complexes owing to unusually large zero-field splitting (D> +200 cm(-1)). The change in ground state electronic configuration is attributed to tailored pincer ligand-to-metal pi-donation within the PNP ligand serie
Keywords: computer chemistry; ligands; magnetic properties; NMR spectroscopy; ruthenium

Superparamagnetic iron oxide nanoparticles as novel x-ray enhancer for low-dose radiation therapy - Klein, Stefanie; Sommer, Anja; Distel, Luitpold; Hazemann, Jean-Louis; Kroener, Wolfgang; Neuhuber, Winfried; Müller, Paul; Proux, Olivier; Kryschi, Carola (Journal of Physical Chemistry B, 2014)
Superparamagnetic iron oxide nanoparticles (SPIONs) with a mixed phase composition (γ-FeO)(Fe O)and sizes between 9 and 20 nm were synthesized via coprecipitation and were either left uncoated or subsequently surface-stabilized with citrate or malate anions. The sizes, morphology, surface chemistry, and magnetic properties of the nanoparticles were characterized using transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, and superconducting quantum interference device measurements, respectively. Cellular uptake and intracellular distribution in normal tissue and tumor cells were verified by TEM images. X-ray-induced changes of the oxidation state and site geometries of surface iron ions of uncoated and citrate-coated SPIONs were explored by collecting Fe K-edge X-ray absorption spectroscopy data. The potential applicability of citrate- and malate-coated SPIONs as an X-ray enhancer for radiation cancer therapy was substantiated by their drastic enhancement of the concentration of reactive oxygen species (ROS) in X-ray irradiated tumor cells. © 2014 American Chemical Society.

Synthesis, magnetic properties, and STM spectroscopy of an unprecedented octanuclear chloro-bridged nickel(II) double cubane. - Scheurer, Andreas; Gieb, Klaus; Alam, Mohammad S.; Heinemann, Frank Wilhelm; Saalfrank, Rolf; Kroener, Wolfgang; Petukhov, Konstantin; Stocker, Michael; Müller, Paul (Dalton Transactions, 2012)
Reaction of nickel(II) chloride hexahydrate with N-n-butyldiethanolamine H(2)L (3) in the presence of LiH in anhydrous THF leads to the formation of the unique octanuclear chloro-bridged nickel(II) double cubane [(Ni(II)(4)(μ(3)-OH)Cl(3)(HL)(3)μ(2)-Cl)(2)] (4) in 57% yield. According to single crystal X-ray structure analysis, complex 4·4CH(2)Cl(2) possesses a [(Ni(4)(μ(3)-OH)(μ(3)-O)(3)(OH)(3)(N)(3)(Cl)(3)μ(2)-Cl)(2)] core and crystallizes in the monoclinic space group P2(1)/c with a = 18.292(2), b = 19.8972(5), c = 23.295(2) Å, β = 98.408(6)°, V = 8387.3(8) Å(3), and four molecules in the unit cell. The analysis of the SQUID magnetic susceptibility data identified 4 as a weakly coupled dimer (J(1) = 14.5 K, J(2) = -0.6 K) with a ground state of S = 0, resulting from two S = 4 states of each Ni(4) subunits. Although complex 4 does not show an ac out-of-phase signal in a zero dc field at temperatures of 1.8 K and higher, low-temperature magnetization measurements revealed that complex 4 is a single-molecule magnet and shows hysteretic magnetization characteristics with typical temperature and sweep-rate dependencies. The eye-catching feature of complex 4 is the presence of two different blocking temperatures (0.9 K around zero field and 1.3 K at higher fields). The origin of this highly unusual behavior can be assigned to the dimer-nature of the interaction between the two S = 4 units. Furthermore STM and current imaging tunnelling spectroscopy (CITS) were performed on aggregates of 4 drop-coated on highly oriented pyrolytic graphite (HOPG) surfaces. CITS measurements show a strong contrast in the area of the nickel centers and a HOMO-LUMO gap of approximately 0.8 V.

Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.